Pengaruh Corporate Social Responsibility Terhadap Citra Perusahaan PT Pertamina Geothermal Energy Area Kamojang (Studi Terhadap Masyarakat Daerah Kamojang) - Amin, Fajar Fathul; Rahmadi, Adi (International Journal Administration, Business & Organization, 2023)
This study aims to find out how Corporate Social Responsibility (CSR) and the corporate image of PT Pertamina Geothermal Energy Area Kamojang are, and how much influence CSR has on the corporate image of PT Pertamina Geothermal Energy Area Kamojang. This study used an explanatory survey method with a sample of 177 which were analyzed using descriptive statistics and simple linear regression. The results of the study stated that the influence of Corporate Social Responsibility on corporate image was 19.6%, while the remaining 80.4% was influenced by other factors. This research can be improved again by adding other variables and increasing the sample size and involving more stakeholders such as company employees and managers.